The stranger in early modern and modern Jewish tradition - Bartlett, Catherine 1967-; Schlör, Joachim 1960- (Studies in Jewish history and culture, 2021)
"Angels are the ultimate stranger. They come from another world and have a special place in the art of the Russian Jewish painter Marc Chagall (1887-1985). In My Life (1923) the young Chagall recalls one memorable night in Saint-Petersburg. Drifting into sleep in the corner of a room (all he could afford) he suddenly saw the ceiling open and a winged being, surrounded by light and blue air, hovered above him before disappearing through the ceiling again."